Given:
CosA = 1/√37
Cos B = 1/√2
Using the identity below:
![\text{Cos(A}+B)=\cos A\cos B-\sin A\sin B](https://img.qammunity.org/2023/formulas/mathematics/high-school/qzhhgbb0mdxye3ortlumwnsu2o9ak4ytpo.png)
We need to find sinA
Using the identity
cos²A + sin²A= 1
Substitute cosA = 1/√37 into the above and solve for sinA
(1/√37) ² + sin²A = 1
1/37 + sin²A = 1
Subtract 1/37 from both-side of the equation
sin²A = 1- 1/37
![\sin ^2A=(37-1)/(37)=(36)/(37)](https://img.qammunity.org/2023/formulas/mathematics/high-school/wcslc5uwc0vh1c7j0sr8o0n46bpjc254me.png)
Take the square root of both-side
![\sin A=\pm\sqrt[]{(36)/(37)}=\pm\frac{6}{\sqrt[]{37}}](https://img.qammunity.org/2023/formulas/mathematics/high-school/ngthkne5kox7ad0r9ki2uusejvfhvwylrm.png)
But sinA is in the first quadrant, hence it is positive.
sinA = 6/√37
Next, is to find the value of sinB.
cos²B + sin²B= 1
Substitute for cosB and solve for sinB.
(1/√2)² + sin²B = 1
1/2 + sin²B = 1
Subtract 1/2 from both-side of the equation.
sin²B = 1 - 1/2
![\sin ^2B=(2-1)/(2)=(1)/(2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/75l5c303h6b8dnpsdxhnd1bmoqx77ojyoe.png)
Take the square root of both-side of the equation.
![\sin B=\pm\frac{1}{\sqrt[]{2}}](https://img.qammunity.org/2023/formulas/mathematics/high-school/dou15rz5ik5bb24a22jujzqf9eh5dh54uj.png)
sine is positive in the first quadrant, hence sinB = 1/√2
We can now proceed to solve for cos(A+B)
![\text{Cos(A}+B)=(\frac{1}{\sqrt[]{37}})(\frac{1}{\sqrt[]{2}})-(\frac{6}{\sqrt[]{37}})(\frac{1}{\sqrt[]{2}})](https://img.qammunity.org/2023/formulas/mathematics/high-school/43mhyz7eyd2n4yhgfy6pf8yg37db6klwpk.png)
![=\frac{1}{\sqrt[]{74}}-\frac{6}{\sqrt[]{74}}](https://img.qammunity.org/2023/formulas/mathematics/high-school/jm3mn109q4m8g0mkc0vq0j4wjr3mpqo826.png)
![=-\frac{5}{\sqrt[]{74}}](https://img.qammunity.org/2023/formulas/mathematics/high-school/9zg2e21xky3o79np0odcl1p9uox2jvipmy.png)